2019
DOI: 10.1002/biof.1588
|View full text |Cite
|
Sign up to set email alerts
|

Retraction

Abstract: Diabetes, is the eighth cause of death worldwide, is a kind of metabolic disease. We planned to study the potentials of the angelica polysaccharide (AP) in MIN6 cell line. Cells were induced with tumor necrosis factor α (TNF-α) dilution or APsolutions, and transfected with microRNA-143 (miR-143) as well as the corresponding negative control (NC). Viability was assessed via CCK-8, while the apoptosis rate was tested by the Annexin V-FITC/PI as well as flow cytometer. The insulin, miR-143 and relative proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been shown that pachyman in P-DSS can activate PPAR by inhibiting p38 MAPK phosphorylationγ The pathway protects the kidney damage of model mice, and Western blot results show that with the increase of pachyman concentration, the level of p-p38 MAPK in kidney tissue gradually decreases, PPAR-γ The level rises gradually [90]. In addition, Angelica polysaccharide blocks NF in MIN6 cells-κ B and p38 MAPK to promote miR-143 and release TNF-α Induced damage, TNF-α Induction can inhibit pancreatic insulin secretion and reduce insulin activity [91]. The drug "Poria cocos Alisma" can activate the expression of AMPK signal pathway and inhibit its downstream targets ACC, SREBP-1C, PCSK9, PPAR γ、 HMGCR expression affects cholesterol and fatty acid metabolism [92].…”
Section: Effect Of Signaling Pathways On Dm Effect Of Mapk Signaling ...mentioning
confidence: 99%
“…It has been shown that pachyman in P-DSS can activate PPAR by inhibiting p38 MAPK phosphorylationγ The pathway protects the kidney damage of model mice, and Western blot results show that with the increase of pachyman concentration, the level of p-p38 MAPK in kidney tissue gradually decreases, PPAR-γ The level rises gradually [90]. In addition, Angelica polysaccharide blocks NF in MIN6 cells-κ B and p38 MAPK to promote miR-143 and release TNF-α Induced damage, TNF-α Induction can inhibit pancreatic insulin secretion and reduce insulin activity [91]. The drug "Poria cocos Alisma" can activate the expression of AMPK signal pathway and inhibit its downstream targets ACC, SREBP-1C, PCSK9, PPAR γ、 HMGCR expression affects cholesterol and fatty acid metabolism [92].…”
Section: Effect Of Signaling Pathways On Dm Effect Of Mapk Signaling ...mentioning
confidence: 99%